THE INFLUENCE OF POWTOON MEDIA IN TEACHING LISTENING - Gerry Heryanto; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2021)
The development of technology and information greatly affect the use of media as a tool in teaching process. The role of the teacher here is not just to convey the material, but is expected to be able to utilize the technology to support teaching and learning activities, the selection of appropriate learning media is very influential on the achievement of educational goals. The purpose of this study was to determine how the influence of the use of powtoon media in the process of learning listening in eighth grade students at one of the junior high schools in Cimahi. The research method used is descriptive qualitative. Subjects in this research were eighth grade students with a total 25 students consisting of 10 male students and 15 female students. The instrument used was a questionnaire with 10 statement items, consisting of 5 positive statements and 5 negative statements. The results of this study indicate that the influence of the use of powtoon as a media in learning listening of eighth grade students at one of junior high schools in Cimahi is categorized very well with an average percentage of 100%. Keywords:  Case Study, Listening, Powtoon Media